In Vitro Study of Amniotic Fluid Gram Stain: Effect of Centrifugation - Daniel W. Gauthier; Wilfredo Torres; William J. Meyer; Barbara G. Lewis; Michael O. Vernon; William M. Janda (Hindawi Limited, 1994)
Objective: Gram stain of amniotic fluid (AF) is used to detect intraamniotic infection. The purpose of this study was to determine if centrifugation improved the ability of AF Gram stain to detect bacteria.